Diversity Promotes Temporal Stability across Levels of Ecosystem Organization in Experimental Grasslands - Proulx, Raphaël; Wirth, Christian; Voigt, Winfried; Weigelt, Alexandra; Roscher, Christiane; Attinger, Sabine; Baade, Jussi; Barnard, Romain L.; Buchmann, Nina; Buscot, François; Eisenhauer, Nico; Fischer, Markus; et al. (PLOS ONE, 2010)
The diversity–stability hypothesis states that current losses of biodiversity can impair the ability of an ecosystem to dampen the effect of environmental perturbations on its functioning. Using data from a long-term and comprehensive biodiversity experiment, we quantified the temporal stability of 42 variables characterizing twelve ecological functions in managed grassland plots varying in plant species richness. We demonstrate that diversity increases stability i) across trophic levels (producer, consumer), ii) at both the system (community, ecosystem) and the component levels (population, functional group, phylogenetic clade), and iii) primarily for aboveground rather than belowground processes. Temporal synchronization across studied variables was mostly unaffected with increasing species richness. This study provides the strongest empirical support so far that diversity promotes stability across different ecological functions and levels of ecosystem organization in grasslands.